A High‐Performance Top‐Gated Graphene Field‐Effect Transistor with Excellent Flexibility Enabled by an iCVD Copolymer Gate Dielectric. Issue 9 (18th December 2017) - Oh, Joong Gun; Pak, Kwanyong; Kim, Choong Sun; Bong, Jae Hoon; Hwang, Wan Sik; Im, Sung Gap; Cho, Byung Jin
Abstract: A high‐performance top‐gated graphene field‐effect transistor (FET) with excellent mechanical flexibility is demonstrated by implementing a surface‐energy‐engineered copolymer gate dielectric via a solvent‐free process called initiated chemical vapor deposition. The ultrathin, flexible copolymer dielectric is synthesized from two monomers composed of 1, 3, 5‐trimethyl‐1, 3, 5‐trivinyl cyclotrisiloxane and 1‐vinylimidazole (VIDZ). The copolymer dielectric enables the graphene device to exhibit excellent dielectric performance and substantially enhanced mechanical flexibility. The p ‐doping level of the graphene can be tuned by varying the polar VIDZ fraction in the copolymer dielectric, and the Dirac voltage ( V Dirac ) of the graphene FET can thus be systematically controlled. In particular, the V Dirac approaches neutrality with higher VIDZ concentrations in the copolymer dielectric, which minimizes the carrier scattering and thereby improves the charge transport of the graphene device. As a result, the graphene FET with 20 nm thick copolymer dielectrics exhibits field‐effect hole and electron mobility values of over 7200 and 3800 cm 2 V −1 s −1, respectively, at room temperature. These electrical characteristics remain unchanged even at the 1 mm bending radius, corresponding to a tensile strain of 1.28%. The formed gate stack with the copolymer gate dielectric is further investigated for high‐frequency flexible device applications. Abstract : A high‐performance top‐gated graphene field‐effect transistor (FET) with excellent mechanical flexibility is demonstrated by utilizing the imidazole‐containing copolymer gate dielectric via initiated chemical vapor deposition. The Dirac voltage ( V Dirac ) of the graphene FET can be systematically controlled according to the copolymer composition, which enables the suppression of carrier scattering and thereby improves charge transport in the graphene device.